Land-use change and managed aquifer recharge effects on the hydrogeochemistry of two contrasting atoll island aquifers, Roi-Namur Island, Republic of the Marshall Islands. (May 2017) - Hejazian, Mehrdad; Gurdak, Jason J.; Swarzenski, Peter; Odigie, Kingsley O.; Storlazzi, Curt D.
Abstract: Freshwater resources on low-lying atoll islands are highly vulnerable to climate change and sea-level rise. In addition to rainwater catchment, groundwater in the freshwater lens is a critically important water resource on many atoll islands, especially during drought. Although many atolls have high annual rainfall rates, dense natural vegetation and high evapotranspiration rates can limit recharge to the freshwater lens. Here we evaluate the effects of land-use/land-cover change and managed aquifer recharge on the hydrogeochemistry and supply of groundwater on Roi-Namur Island, Republic of the Marshall Islands. Roi-Namur is an artificially conjoined island that has similar hydrogeology on the Roi and Namur lobes, but has contrasting land-use/land-cover and managed aquifer recharge only on Roi. Vegetation removal and managed aquifer recharge operations have resulted in an estimated 8.6 × 10 5  m 3 of potable groundwater in the freshwater lens on Roi, compared to only 1.6 × 10 4  m 3 on Namur. We use groundwater samples from a suite of 33 vertically nested monitoring wells, statistical testing, and geochemical modeling using PHREEQC to show that the differences in land-use/land-cover and managed aquifer recharge on Roi and Namur have a statistically significant effect on several groundwater-quality parameters and the controlling geochemical processes. Results also indicate a six-fold reduction in the dissolution of carbonate rock in the freshwater lens and overlying vadose zone of Roi compared to Namur. Mixing of seawater and the freshwater lens is a more dominant hydrogeochemical process on Roi because of the greater recharge and flushing of the aquifer with freshwater as compared to Namur. In contrast, equilibrium processes and dissolution-precipitation non-equilibrium reactions are more dominant on Namur because of the longer residence times relative to the rate of geochemical reactions. Findings from Roi-Namur Island support selective land-use/land-cover change and managed aquifer recharge as a promising management approach for communities on other low-lying atoll islands to increase the resilience of their groundwater supplies and help them adapt to future climate change related stresses. Highlights: Land use and managed aquifer recharge (MAR) alter hydrogeochemistry on atolls. Land use and MAR create differences in pH, ORP, Ca 2+, NH4 +, TDN, and δ 13 C-DIC. Land use and MAR create annual increase in porosity: 0.004% (Roi), 0.024% (Namur). Changes to land use and MAR may increase groundwater resilience on other atolls.